PENGARUH KEPEMILIKAN INSTITUSIONAL, CAPITAL INTENSITY, INVENTORY INTENSITY, DAN TRANSFER PRICING TERHADAP TAX AVOIDANCE PADA PERUSAHAAN ENERGI YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2018-2022 - Nisa Ramadhani; Zaenal Afifi; Izza Ashsifa (Program Studi Akuntansi, Fakultas Ilmu Sosial dan Humaniora, Universitas Ibrahimy Situbondo, 2024)
Tax avoidance is an effort to reduce the tax burden without violating any laws or other applicable regulations. This study aims to determine the influence of institutional ownership, capital intensity, inventory intensity, and transfer pricing on tax avoidance. This research uses a quantitative method with secondary data obtained from www.idx.com and applies agency theory. The population of this study consists of energy sector companies listed on the Indonesia Stock Exchange for the period 2018-2022. The sampling technique used is purposive sampling with a total of 94 observations. The analytical technique employed in this study is panel data multiple regression analysis using Eviews 12. The results of this study indicate that capital intensity has a negative effect on tax avoidance, while institutional ownership, inventory intensity, and transfer pricing do not affect tax avoidance